Modernisation of passengers stock deposit at the regional division Braşov - SIMA, Elena (Annals of Spiru Haret University. Economic Series, 2010)
The purpose of this paper is to present the latest accomplishments at the Regional Division Brasov regarding the modernisation of stock depot for passengers but also future programs that will continue this process. The rolling stock used in passenger transport was followed: passenger wagons, sleeping wagons, diesel engines, electric engines. Passenger transport organisation should aim the accomplishment of the following requirements: ensuring passengers’ security on the route and in stations; reducing travel time (by increasing trains’ speed, choosing the best routes, reducing stops at stations, ensuring certain fast links at railway junctions); intensive usage of rolling stock, of fixed installations; the appropriate combination of freight with passenger transport, passengers’ good serving at stations and trains, especially by ensuring a timetable which would provide convenient hours and reliable connections at railway junctions.